Decision points in mathematics lectures. Issue 6 (2nd November 2018) - O'Shea, Ann; Breen, Sinead; Meehan, Maria
Abstract: We report on a study of decision-making in mathematics lectures. The data comes from accounts of classroom incidents written over two academic years by three university mathematics lecturers who set out to reflect on, and improve, their practice by collectively engaging in a professional development project using Mason's Discipline of Noticing. The accounts were analysed to locate decision points during lectures. We report on a classification of these decision points and give examples. We found that 72% of the decision points that occurred were student-focussed while the remainder focussed on the practice of teaching. The professional development implications of our study will be discussed.